The Development of a Large-Area Microchannel Plate Photomultiplier Tube with a Gate Function - Ziyu Liu; Hulin Liu; Ping Chen; Kuinian Li; Yonglin Wei; Luanxuan He; Xinnan Zhao; Wei Zhao; Jinshou Tian (Photonics)
To meet the application requirements of neutron detectors, a novel large-area microchannel plate photomultiplier tube with a gate function (G-MCP-PMT) was developed in this study. A kind of regular hexagonal mesh electrode as the gated electrode was designed to achieve excellent gating functions for target pulse signals. The photoelectron transmittances for different mesh electrode sizes and voltages were studied via numerical simulations. To increase the effective detection area of the photocathode, an electrostatic-focusing electrode was designed in the G-MCP-PMT. By optimizing the structure of the focusing electrode, an effective photocathode detection surface diameter of 80 mm was achieved based on commercially available MCPs with a diameter of 56 mm. By adjusting the channel diameter configurations of the dual MCPs, the output pulse peak and time response of the large-area G-MCP-PMT can be flexibly adjusted. The experimental results indicate that when the large-area G-MCP-PMT is operated at −2700 V, the gate establishment time is approximately 50 ns. The extinction ratio of the large-area G-MCP-PMT is higher than 3000:1, and the maximum linear output current is greater than 300 mA at 250 ns FWHM, meeting application needs in various fields such as white neutron detection and laser radar.